2018
DOI: 10.1002/hep.29902
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PDK4 switches the hepatic NF‐κB/TNF pathway from pro‐survival to pro‐apoptosis

Abstract: PDK4 is indispensable to dictate the fate of TNF/NF-κB-mediated hepatocyte apoptosis. (Hepatology 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 45 publications
2
68
1
Order By: Relevance
“…In the priming phase of PHx, the Kupffer cell–derived tumor necrosis factor (TNF) primes hepatocytes to re‐enter into the cell cycle . Pdk4 deficiency facilitates TNF expression . It will be interesting to determine the role of PDK4 in the priming phase after PHx as well as the hepatic activation of other signaling pathways during LR under Pdk4 ‐deficient conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the priming phase of PHx, the Kupffer cell–derived tumor necrosis factor (TNF) primes hepatocytes to re‐enter into the cell cycle . Pdk4 deficiency facilitates TNF expression . It will be interesting to determine the role of PDK4 in the priming phase after PHx as well as the hepatic activation of other signaling pathways during LR under Pdk4 ‐deficient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…(11,33) Pdk4 deficiency facilitates TNF expression. (17) It will be interesting to determine the role of PDK4 in the priming phase after PHx as well as the hepatic activation of other signaling pathways during LR under Pdk4-deficient conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 More importantly, a recent study demonstrated that genetic loss of PDK4 resulted in spontaneous cell death of human hepatocellular carcinoma cells (HCC), which was accompanied by mitochondrial dysfunction and increased production of ROS. 34 Moreover, PDK4-deficient mice suffered from increased chemically-induced liver injury, which could be prevented by inhibition of the NF- k B subunit p65. 34 These recent findings highlight the potential of PDK4 over-expression to alleviate chemically-induced liver injury and to reduce hepatic ROS levels, which is confirmed by the results outlined in our present study.…”
Section: Discussionmentioning
confidence: 99%